Africa on film : beyond black and white - Cameron, Kenneth M., 1931- (Continuum, 1994)
From serious social commentary to outrageous camp, from Cry, the Beloved Country to Tarzan and Jungle Queen, American and British films have gone to Africa, either in spirit or reality, to find the treasures that lie there. More than four hundred films have been made about (or in) Africa in the English language, from the beginning of Edison films in the first decade of the twentieth century up to the present. They range from endless "B" movies and boys' adventure films, to the ever-popular animal documentaries and safari docudramas, to serious efforts to understand colonialism and African-American identity. Together they make a fascinating montage of European and American projections - and even occasionally offer an accurate portrait of a continent and its varied peoples.